ANXIETY AND STRESS OF HEALTHCARE WORKERS AT QUANG NINH MENTAL HEALTH PROTECTION HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: The study aims to describe the current situation and analyze some factors related to anxiety and stress of healthcare workers.Method: Cross-sectional descriptive study on 151 healthcare workers at Quang Ninh Mental Health Protection Hospital using the DASS-21 toolkit.Results: The rate of healthcare workers showing signs of anxiety was 21.2%. The levels of mild, moderate, severe, and very severe anxiety disorders were: 4.6%; 8.0%; 3.3%; and 5.3%, respectively. The rate of healthcare workers showing signs of stress was 13.9%. The levels of mild, moderate, severe, and very severe stress are: 1.3%; 1.3%; 2.7%; and 8.6%, respectively. Factor related to anxiety of healthcare workers was: education level. Factors related to stress were: education level, caring for elderly relatives and number of night shifts in 1 month.Conclusion: The hospital needs to conduct repeated screening to detect signs of stress and anxiety in healthcare workers, in order to have support measures; develop salary and welfare mechanisms, improve and enhance working conditions for healthcare workers.
Keywords: Anxiety, stress, healthcare workers, DASS-21.